Taḥlīl al-akhtāʾ al-shafahiyyah al-shāʾiʿah ladā ṭullāb Maʿhad Mafāzā Indūnīsiyā - Marlina, Lina; Setia Budi, Firmansah (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
When a person learns a second language, he already has a perfect language system in the form of his first language or also called his native language. Therefore, we often find the occurrence of language interference, namely the involvement of the rules or systems of the first language into the rules or systems of the target language in various language components, such as phonological, syntactic, morphological and semantic components. Not a few of the language learners think that the meaning in a sentence that he often finds in the structure of his first language he can also use in the structure of the target language only by changing the language of the sentence. Perhaps among the causes of this is the dependence of students on translation from the first language into the target language during the learning process. Errors in this language may continue to accompany the student even though he is not a beginner anymore, this will happen if the curriculum makers are not paying attention to the problem, or the teachers do not correct the mistakes as early as possible. Teachers must be able to convince students that language styles differ from one language to another as well as vocabulary differences. Students must also be given an understanding that an expression with a certain meaning in their first language, may have a different meaning in the target language. Even if the same meaning of the expression is also found in the target language, perhaps the meaning will be expressed in a different sentence. Therefore, this research was prepared with the aim of collecting common errors of Indonesian Mafaza students in language using descriptive analysis method. As a result, the authors found at least 49 errors in language that were often spoken by the students, then the authors included the correct way of expressing each of these language errors, so that they could be a reference for the students or anyone who reads this article about how to express the intended meaning, the right way in Arabic.